Heparin and Related Substances for Treating Diabetic Foot Ulcers: A Systematic Review and Meta-Analysis - Su, Na; Xu, Ting; Li, Xiaodan; Zheng, Hanrui; Wu, Bin; Zhang, Shengzhao; Zhou, Yiling; Du, Liang; Zhao, Yinglan (Frontiers in Endocrinology, 2022)
Background: Diabetic foot ulcers are a major complication of diabetes mellitus (DM), when heparin and heparin-related substances may be potentially used as an adjuvant treatment. We aimed to evaluate the efficacy and safety of heparin and heparin-related substances for the treatment of diabetic foot ulcers. Methods: We searched up to March 2021 in the Cochrane Central Register of Controlled Trials (CENTRAL); Ovid MEDLINE; Ovid Embase; EBSCO CINAHL; VIP Chinese Science and Technique Journals Database; China National Knowledge Infrastructure (CNKI) Database and Wan Fang Database investigating heparin or heparin-related substances in patients with diabetic foot ulcers. The primary outcomes included proportion of ulcers completely healed and time to complete ulcer healing. We assessed each included study with the Cochrane 'Risk of bias' tool and used the GRADE approach to assess the overall quality of the evidence. Results: We included nine randomized studies involving 620 participants in the meta-analysis, involving two different heparin and heparin-related substances, low molecular weight heparin (LMWH) and hyaluronic acid. Our study did not show the benefits from LMWH on increasing chance of the ulcer healing (RR: 1.26; 95% CI: 0.78 to 2.04; P=0.35; very low) or shortening the time to complete ulcer healing (SMD: 0.13 d; 95% CI: -0.29 to 0.56; P=0.54; very low). Hyaluronic acid may improve the complete ulcer healing (RR: 1.57; 95% CI: 1.29 to 1.91; P˂0.00001; very low), and shorten the time to complete ulcer healing (SMD -0.84, 95% CI -1.15 to -0.53; P<0.00001; low). Current evidence did not identify significant safety issues of LMWH or hyaluronic acid compared to conventional therapy. Conclusion: Hyaluronic acid may improve diabetic foot ulcer with very low quality evidence but not LMWH (very low). However, the benefits and harms need further validation in larger trials with different population.